Intradermal injection of human adipose-derived stem cells accelerates skin wound healing in nude mice. Issue 1 (December 2015) - Rodriguez, Jonathan; Boucher, Fabien; Lequeux, Charlotte; Josset-Lamaugarny, Audrey; Rouyer, Ondine; Ardisson, Orianne; Rutschi, Héléna; Sigaudo-Roussel, Dominique; Damour, Odile; Mojallal, Ali
Abstract Background The use of stem cells from adipose tissue or adipose-derived stem cells (ASCs) in regenerative medicine could be an interesting alternative to bone marrow stem cells because they are easily accessible and available in large quantities. The aim of this study was to evaluate the potential effect of ASCs on the healing of 12 mm diameter-excisional wounds (around 110 mm2 ) in nude mice. Methods Thirty nude mice underwent surgery to create one 12-mm excisional wound per mouse (spontaneous healing, n = 6; Cytocare® 532, n = 12; ASCs, n = 12). The Galiano wound model was chosen to avoid shrinkage and thus slow the spontaneous healing (SH) of mouse skin, making it closer to the physiology of human skin healing. Transparent dressings were used to enable daily healing time measurements to be taken. Immunohistochemistry, histological and blood perfusion analysis were carried out on the healed skin. Results The in vivo results showed the effectiveness of using ASCs on reducing the time needed for complete healing to 21.2 days for SH, 17.4 days for vehicle alone (Cytocare® 532) and 14.6 days with the addition of ASCs (p < 0.001). Moreover, cutaneous perfusion of the healed wound was significantly improved in ASC-treated mice compared to SH group, as shown by laser Doppler flowmetry and the quantitation of blood vessels using immunohistochemistry of αsmooth muscle actin. Conclusions The tolerance and efficacy of cryopreserved ASCs to accelerate the complete closure of the wound by increasing the maturation of the skin and its blood perfusion, s hows their therapeutic benefit in the wound healing context.